The populist explosion : how the great recession transformed American and European politics - Judis, John B. (Columbia Global Reports, 2016)
"Is the West witnessing a huge political upheaval? As if overnight, many Democrats revolted and passionately backed a socialist named Bernie Sanders; the United Kingdom voted to leave the European Union, in a stunning rebuke; the vituperative billionaire Donald Trump became the presidential nominee of the Republican Party; and a slew of rebellious parties continued to win election after election in countries like Switzerland, Norway, Italy, Austria, and Greece. John B. Judis, one of America's most respected political analysts, tells us why we need to learn about the populist movement that began in the United States in the 1890s, the politics of which have recurred on both sides of the Atlantic ever since. Populism, on both the right and the left, champions the people against an establishment, based on issues - globalization, free trade, immigration - on which there has been a strong elite consensus, but also an even stronger mass discontent that is now breaking out in the open"--Cover.